IMAGINARY AUDIENCE, PERSONAL FABLE, DAN PERILAKU AGRESI REMAJA - Azhari, Salma Muthia; Dahlan, Tina Hayati; Musthofa, Muhamad Areiz (JURNAL PSIKOLOGI INSIGHT, 2019)
This study aimed to identify the predictions of imaginary audience and personal fable to the aggression behavior of adolescents in the city of Bandung. Participants of the study were 395 adolescents that range 13-18 years old, selected by cluster random sampling techniques. The research data was collected by the New Imaginary Audience Scale (NIAS), the New Personal Fable Scale (NPFS), and the Buss-Perry Aggression Questionnaire that had been adapted into Indonesian. Processing data research using simple and multiple linear regression analysis. The results of this study indicate that there was significantly effect of imaginary audience and personal fable on agression behavior. Simultaneously the contribution of imaginary audience and personal fable to adolescent aggression behavior in Bandung is 12 percent. The contribution of imaginary audience to adolescent aggression behavior is partially higher than personal fable contribution.